Electrical type conversion of p-type HgCdTe induced by nanoimprinting - Martyniuk, M.; Sewell, R.; Westerhout, R.; Umana-Membreno, G.; Musca, C.; Dell, J.; Antoszewski, J.; Faraone, L.; MacIntyre, D.; Thoms, S.; Ironside, Charlie (2011)
A nanoimprinting method was used to generate square imprints and arrays of imprints ranging in lateral dimension from 1 m to 50 µm in p-type HgCdTe. Laser Beam Induced Current (LBIC) characterization shows electrical type conversion around each imprint and imprint array. The LBIC signal intensity surface maps of imprinted regions and their dependence with measurement temperature correspond well with surface maps of n-on-p HgCdTe photodiodes formed by conventional techniques.